Sequential deposition of multicomponent bulk heterojunctions increases efficiency of organic solar cells - Xu, Xiaopeng (2023)
Constructing tandem and multi-blend organic solar cells (OSCs) is an effective way to overcome the absorption limitations of conventional single-junction devices. However, these methods inevitably require tedious multilayer deposition or complicated morphology-optimization procedures. Herein, sequential deposition is utilized as an effective and simple method to fabricate multicomponent OSCs with a double-bulk heterojunction (BHJ) structure of the active layer to further improve photovoltaic performance. Two efficient donor-acceptor pairs, D18-Cl:BTP-eC9 and PM6:L8-BO, are sequentially deposited to form the D18-Cl:BTP-eC9/PM6:L8-BO double-BHJ active layer. In these double-BHJ OSCs, light absorption is significantly improved, and optimal morphology is also retained without requiring a more complicated morphology optimization involved in quaternary blends. Compared to the quaternary blend devices, energy loss (Eloss ) is also reduced by rationally matching each donor with an appropriate acceptor. Consequently, the power conversion efficiency (PCE) is improved from 18.25% for D18-Cl:BTP-eC9 and 18.69% for PM6:L8-BO based binary blend OSCs to 19.61% for the double-BHJ OSCs. In contrast, a D18-Cl:PM6:L8-BO:BTP-eC9 quaternary blend of OSCs exhibited a dramatically reduced PCE of 15.83%. These results demonstrate that a double-BHJ strategy, with a relatively simple processing procedure, can potentially enhance the device performance of OSCs and lead to more widespread use.